2021
DOI: 10.3324/haematol.2021.279037
|View full text |Cite
|
Sign up to set email alerts
|

Survival in mantle cell lymphoma after frontline treatment with R-bendamustine, R-CHOP and the Nordic MCL2 regimen – a real world study on patients diagnosed in Sweden 2007-2017

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Results from chemoimmunotherapy were also evaluated in real‐world 126 retrospective analyses, and they further establish the data from clinical trials and demonstrate an improvement in patient survival by era 127 …”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Results from chemoimmunotherapy were also evaluated in real‐world 126 retrospective analyses, and they further establish the data from clinical trials and demonstrate an improvement in patient survival by era 127 …”
Section: Introductionmentioning
confidence: 74%
“…Maintenance rituximab after BR did not demonstrate an improvement in outcomes. 125 Results from chemoimmunotherapy were also evaluated in realworld 126 retrospective analyses, and they further establish the data from clinical trials and demonstrate an improvement in patient survival by era. 127 Nonchemotherapy options-Lenalidomide with rituximab was investigated in 38 patients.…”
Section: Prognostic Factorsmentioning
confidence: 83%
“…A previous retrospective study comparing the efficacy of R-bendamustine, R-CHOP, and MCL2 as frontline therapies showed similar age, ECOG, and MIPI class distribution in MCL2-treated patients. 10 We observed an increase in MIPI high-risk patients in the trial-ineligible group (37.7%), and the inclusion of ECOG 3-4 patients, showing that aggressive disease presentation is an important factor in selecting treatment strategies in clinical practice.…”
mentioning
confidence: 72%
“…Among trial‐ineligible patients, the median OS was also remarkable (9.8 years). Albertsson‐Linblad and colleagues 10 reported a median OS of 4.9 years in patients receiving any systemic therapy in the frontline and also showed that both MCL2 and RB are superior over R‐CHOP. We observed that the PFS improvement was greater in trial‐eligible patients than in trial‐ineligible patients (6.4 versus 4.4 years).…”
Section: Other Mcl2 Trial Eligible Trial Ineligible Clinical Mcl2 Trialmentioning
confidence: 99%
“…25 In a real-world study of patients diag nosed in Sweden between 2007 and 2017, for patients under 70 years of age there was no sig nifi cant dif fer ence in OS with inten sified MCL2 pro to col or R-CHOP com pared to bendamustinerituximab. 31 Additionally, it may be pos si ble to con sider the defer ral of ASCT to the relapsed/refrac tory (R/R) set ting. There are data to sug gest that ASCT can be effec tive in CR2, although it is unclear whether out comes are equiv a lent to up-front ASCT.…”
Section: Clinical Casementioning
confidence: 99%